Top spoilage losses for corn and forage sorghum silages stored in bunker silos - Holthaus, D.L.; Dalke, B.S.; Pfaff, L.; Boyer, John E.; Bolsen, K.K.; Young, Matthew A. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Corn and forage sorghum silages were stored in small bunker silos for 180 days. Dry matter (DM) and organic matter (OM) losses, fermentation characteristics , in-situ DM digestibility, and temperatures were measured at 10, 20, and 30 inches from the original silage surface. Sealing the exposed surface increased DM and OM recoveries and improved fermentation quality and nutritive value in both crops, regardless of depth. The unsealed corn silages were much hotter within the top 3 ft than sealed silages, indicating aerobic losses. As expected , the unsealed silages from both crops deteriorated severely i n the top 20 inches. Placing a roof over the unsealed silos increased the silage DM content at all three depths, but did not consistently improve the storage efficiency or silage quality of either crop.
Keywords: Beef; Silage; Top spoilage; Corn; Sorghum